2007
DOI: 10.1128/jvi.01457-07
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-6 and Claudin-9 Function as Additional Coreceptors for Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) is a global challenge to public health. Several factors have been proven to be critical for HCV entry, including the newly identified claudin-1 (CLDN1). However, the mechanism of HCV entry is still obscure. Presently, among the 20 members of the claudin family identified in humans so far, CLDN1 has been the only member shown to be necessary for HCV entry. Recently, we discovered that Bel7402, an HCV-permissive cell line, does not express CLDN1 but expresses other members of claudin fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
190
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(199 citation statements)
references
References 40 publications
7
190
0
2
Order By: Relevance
“…As shown with serum-derived virus, HCV uses various processes to enter target cells, and HCVpp infection of Huh7-cells is a surrogate model for most entry pathways, including the CD81 route used here, its sole lack being entry mediated by virus when associated with lipoproteins (11,12,30,(35)(36)(37)(38)(39). In this system, CD81 and E2 clearly have a major role because anti-E2 antibodies and soluble CD81 interfere with virus entry (24,39).…”
Section: Discussionmentioning
confidence: 94%
“…As shown with serum-derived virus, HCV uses various processes to enter target cells, and HCVpp infection of Huh7-cells is a surrogate model for most entry pathways, including the CD81 route used here, its sole lack being entry mediated by virus when associated with lipoproteins (11,12,30,(35)(36)(37)(38)(39). In this system, CD81 and E2 clearly have a major role because anti-E2 antibodies and soluble CD81 interfere with virus entry (24,39).…”
Section: Discussionmentioning
confidence: 94%
“…Claudins are also cell surface receptors for epithelial pathogens. Claudins-3 and -4 are receptors for C. perfringens enterotoxin (93), while claudins-1, -6. and -9 are coreceptors for cellular entry of the hepatitis C virus (29,119). Finally, changes in claudin expression are often associated with epithelial cancers and may potentially play a role in their pathogenesis (74).…”
Section: Role Of Claudins In Human Diseasesmentioning
confidence: 99%
“…CLDN9 is expressed in the liver, the primary site of HCV replication, and peripheral blood mononuclear cells, an additional site of HCV replication. Sequence comparison and mutagenesis studies, showed that residues N38 and V45 in the first extracellular loop of CLDN9 are necessary for HCV entry (Zheng et al, 2007). Claudin-9 expressed in CD81+ (tetraspanin) cells also enables the entry of HCV pseudoparticles.…”
Section: Hepatitis C Virus Infectionmentioning
confidence: 99%